PELATIHAN MANAJEMEN BAGI PENGELOLA BADAN USAHA MILIK DESA (BUMDES) DAN IBU-IBU PKK DI KECAMATAN TEGALWERU DAU KABUPATEN MALANG - Mohammad Maskan; Bambang Soepeno; Tundung Subali Patma; Yulis Nurul Aini (Jurnal Pengabdian Polinema Kepada Masyarakat, 2021)
The goal of the local government is to provide some assistance to the villagers to stimulate the community to actively participate in local potential-based development. Therefore, BUMDes in an effort to strengthen the village economy based on the needs and potential of villages (agriculture), in order to increase the income and welfare of the villagers. The establishment of village-owned enterprises has several legal foundations that are the basis and reference in all its activities. The establishment of village-owned enterprises (BUMDes) is based on Law No. 32 of 2004 on Local Government and Government Regulation No. 72 of 2005 on Village Article 78. BUMDeS managers hold the key to success in its operationalization, therefore management training for BUMDeS managers supported by the PKK is urgently needed to improve the welfare of the villagers. This needs to be mastered by the managers of BUMDeS and PKK in order to manage their organizations through good planning, organizing, direction and supervision so that the organization's objectives can be achieved effectively and efficiently.